ANTIVIRAL EFFICACY OF GARLIC OIL AGAINST NEWCASTLE DISEASE VIRUS - Arwa AL-Saeed; Manar Mohammed Hizam Hizam (Basrah Journal of Veterinary Research)
Newcastle disease is a highly contagious and devastating viral disease ofpoultry that distributed worldwide causing large economic losses in the poultryindustry. Although vaccines are being used to control the disease, there is no effectiveantiviral drug used for the treatment of infections. The aim of this study is to testgarlic oil for its antiviral activity against Newcastle disease virus. Garlic oil wasincubated with the virus (LaSota strain) for 1 hr and 24 hrs and its antiviral effect wasdetermined by performing hemagglutination and RT-PCR tests to detect viral surfaceproteins and viral genome, respectively. In addition, the toxicity of garlic oil wasdetermined on the living organism by injecting it into chicken embryos with orwithout the virus. The results showed that this product played a role in the reductionof virus effectiveness through the destroying of viral surface receptors as well as thereduction of gene amplification as compared with the control group that included thetreatment of the virus with a saline solution (phosphate buffer saline), which gaveopposite results. In addition, there was no antiviral toxicity on the living organismsince the injected embryos with the oil alone or the oil with virus were healthy andclosely resemble those that have not been injected with anything. In comparison, theembryos that were injected with the virus only showed clear pathological signs thatdid not appear in the other groups containing the oil. These results suggest that garlic oil would be a good potential antiviral and probably will have a role to eliminate thedisease.